Comparison of EuroSCORE II with EuroSCORE in Cardiac Surgical Patients in a Tertiary Level Teaching Hospital in Nepal - Pradhan, Bishwas; Bastola, Priska; Basnet, Madindra B; Shrestha, Bibhush; Sigdel, Shailendra; Gurung, Arjun (Journal of Institute of Medicine Nepal, 2020)
Introduction European System for Cardiac Operative Risk Evaluation (EuroSCORE) is the standard tool for risk stratification of patients undergoing cardiac surgery. Its relevance has been validated in European, Asian countries and also in Nepal. Its limitations led to development of EuroSCORE II. This study was carried out to compare EuroSCORE II with EuroSCORE in Nepalese cardiac surgical patients. Methods A retrospective analytical cohort study of 3 years duration in 972 adult cardiac surgeries was conducted. Scores obtained from EuroSCORE (Logistic and Additive) and EuroSCORE II was compared with the observed mortality. Calibration was calculated by Hosmer- Lemeshow (H-L) test (Chi Square test) and discrimination by calculating the area under the curve (AUC) of receiver operating characteristics (ROC) curve. Results Observed mortality was 4.11%. EuroSCORE additive, logistic and EuroSCORE II predicted mortality were 4.32%, 4.55% and 2.13% respectively. H-L chi square calculation for EuroSCORE additive model could not hold as all observed and expected frequencies match exactly. Hence it can be considered as a good fit. EuroSCORE logistic model (H-L, Chi-square 7.743, p<0.001) and EuroSCORE II (H-L, Chi-square 11.631, p = 0.168) also showed good fit i.e. both can predict mortality satisfactorily. AUC of ROC curve of EuroSCORE additive, logistic and EuroSCORE II were 0.632, 0.636 and 0.616 respectively, which showed fair discrimination power. Conclusion Mortality prediction of adult cardiac surgical patients by EuroSCORE (additive and logistic) and EuroSCORE II was satisfactory.